SAT0338 Tolerance and efficacy of a new formulation of diacerein: Results of a multicenter, randomized, double-blind, controlled trial in patients with knee osteoarthritis. (23rd January 2014) - Chevalier, X.; Richette, P.; Rannou, F.; Avouac, B.; Dapoigny, M.; Ducrotte, P.; Jean Louis, D.; Savarieau, B.; Blanc, D.; Marty, M.
Abstract : Background: Diacerein [Symptomatic Slow-Acting Drugs in Osteoarthritis (SYSASOA)], has demonstrated its efficacy in patients with hip or knee osteoarthritis in several randomized placebo controlled clinical trials. The efficacy/safety balance of diacerein is hampered by occurrence of diarrhea. A bioequivalent new formulation of diacerein (ART GT) (44 mg) was developed in order to reduce diarrhea. Objectives: To test the hypothesis of better gastrointestinal safety of a new diacerein formulation (ART GT) compared to the usual formulation (ART®50) in patients with knee osteoarthritis (KOA). Methods: In a randomised double-blind controlled trial, patients with symptomatic KOA (baseline pain >40 mm on a 0-100 mm visual analogue scale [VAS]) seen by office-based physicians in 2009-2010 were randomly assigned to either ART GT or ART®50 for 3 months (twice daily). The primary end point was the "diarrhea event" related to study drug (adjudicated by an independent committee) over the first four weeks of treatment. A "diarrhoea event" was defined as any of the following criteria: at least 3 stools daily for at least 3 consecutive days, diarrhoea hindering daily life for at least 5 days, diarrhoea of sufficient severity to require discontinuation of the study drugs, diarrhoea of sufficient severity to require the use of anti-diarrheic medications. Secondary endpoints included: pain [VAS]) WOMAC score, patient and investigator overall assessments, response to treatment following OMERACT/OARSI criteria, consumption of NSAIDs/analgesics, global safety over a three months. Results: Of 547 randomised patients, 517 patients were included in the full analysis set. The proportion of patients experiencing at least 1 diarrhea event was significantly smaller in the ART GT group (30.5%) than in the ART®50 group (41.0%) (p=0.01). There were more patients who discontinued the study treatment for TEAE in the ART®50 group (23.5%) than in the ART GT group (15.0%) (p=0.012). Analyses of all efficacy endpoints showed no differences between the two groups: overall, mean decrease of pain of 24 mm and 56% responders on OARSI criteria. Conclusions: The safety profile of ART GT was significantly better than that of ART®50 in regard to gastrointestinal disorders with the same level of efficacy. (ClinicalTrials.gov number 2009-009990-84). Disclosure of Interest: X. Chevalier Consultant for: Negma, P. Richette Consultant for: Negma, F. Rannou Consultant for: Negma, B. Avouac Consultant for: Negma, M. Dapoigny Consultant for: Negma, P. Ducrotte Consultant for: Negma, D. Jean Louis Consultant for: Negma, B. Savarieau: None Declared, D. Blanc Employee of: Negma, M. Marty Consultant for: Negma